Estudio de la longevidad del polen de maíz (Zea mays L.) en el proceso de selección. - Carrillo Castañeda, G; Mendoza Arizmendi, J.L. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
Comparing the values of half life of pollen, estimating the viability by the ability of pollen to font the pollentube under experimental conditions that allows to obtain up to 93 per cent viability, it was found that the highest half-life frequency observed was 285 minutes either in pollen from corn plants developed out of seeds from the 5th cycle of a mass selection process for drought resistance and in the original Zacatecas 58 cultivar The highest frequencies of abortion rates observed in the pollen samples were 2 and 3 for that of the original cultivar Zacatecas 58 and drought resistant selected plants.